Integrated FMEA approach for analyzing cylinder head failure due to thermal mechanisms in internal combustion engines - Wilarso (Integrated Mechanical Engineering Journal, 2026)
Cylinder head is a critical component in internal combustion engines that operates under extreme thermal and mechanical conditions, making it highly susceptible to failure. One of the most common failure modes is cracking, which is primarily associated with overheating and thermal fatigue. However, existing studies often analyze failures descriptively without integrating causal relationships and quantitative risk assessment. This study aims to analyze the failure mechanism of a cylinder head in unit BMGS1740 using an Failure Mode and Effects Analysis (FMEA) approach. FMEA is applied to evaluate and prioritize risks based on Severity (S), Occurrence (O), and Detection (D), resulting in the Risk Priority Number (RPN). The analysis is based on operational data, inspection results, and thermal performance indicators. The results show that cylinder head failure is driven by a progressive thermal mechanism initiated by cooling system degradation, leading to overheating, thermal stress, and ultimately crack formation. The highest risk factors identified are radiator fouling, water pump failure, and thermal fatigue, each with RPN values ≥ 300, indicating their dominant contribution to failure. Medium-risk factors include thermostat malfunction, loose fan belt, and poor atomization, while overfueling is categorized as a low-risk contributing factor. The findings indicate that cooling system performance is the primary triggering factor, while thermal fatigue acts as the main damage propagation mechanism. Therefore, preventive strategies should focus on improving cooling system efficiency and optimizing combustion processes to minimize thermal loading. This integrated approach provides a more comprehensive framework for failure analysis and supports risk-based maintenance decision-making